Screening of Rhizobacteria Associated with Cassava for Plant Growth Promotion and Biocontrol Potential - Suja, S P; Hegde, Vinayaka; THANGARAJ, Makes Kumar; IP, Anjanadevi (JOURNAL OF ROOT CROPS, 2015)
Plant growth promoting rhizobacteria (PGPR) are beneficial bacteria that colonise plant roots and enhance plant growth by a wide variety of mechanisms. The use of PGPR is steadily increasing in agriculture and offers an attractive way to replace chemical fertilizers, pesticides and supplements. In the present study, rhizobacteria associated with five varieties of cassava, viz., Sree Padmanabha, Sree Vijaya, Sree Jaya, Sree Rekha and Sree Prakash were isolated and screened for their plant growth promotion traits and in vitro biocontrol potential. A total of 41 isolates were selected based on colony morphology and designated as RB1 to RB41. These isolates were screened in vitro for their plant growth promoting traits like production of indole acetic acid (IAA), ammonia (NH3), phosphate solubilisation, hydrogen cyanide (HCN) and antifungal activity. Cowpea seeds were treated with rhizobacteria to assess seed germination and growth of seedlings. A pot experiment was conducted with cassava variety, Sree Vijaya, where stem cuttings were treated with rhizobacteria followed by a soil drench. About 88% of the isolates produced IAA, 83% produced ammonia and 50% solublized P. Only one isolate produced HCN and nine isolates showed antifungal activity against the plant pathogen, Sclerotium rolfsii. Rhizobacterial treatments promoted the germination in cowpea and growth in cassava.The present study suggests that PGPR isolates might have potential in future field applications as plant growth promoters or as biocontrol agents.